The challenge of the quest for excellence - Ostrom, Vincent (1996)
"This collapse of major empires in the twentieth century poses a challenge. Can human civilizations maintain themselves and achieve increasing degrees of complementarity without being driven by imperial aspirations to dominate others? A diagnostic assessment is necessary. Where do we turn in building other foundations for the constitution of order in the decades ahead? An analysis of the intellectual resources of our respective civilizations is necessary with respect to (1) their common features and (2) their distinctive features that enable people to learn from others. The analysis proceeds in terms of (1) the failure of autocratic bureaucracies, (2) fundamental concepts and basic principles of order, and (3) conclusions. In a culture of inquiry, scholarship merges with problem-solving capabilities; and human creativity achieves its place in Creation. Both sympathetic understanding and critical reflections in efforts to be helpful are necessary to productive scholarship and creative artisanship"
Keywords: Public administration - United States; Bureaucracy; Public administration